Venous Thromboembolism in Patients with Liver Cirrhosis: Findings from the RIETE (Registro Informatizado de la Enfermedad TromboEmbolica) Registry - Bikdeli, Behnood; Jiménez, David; Garcia-Tsao, Guadalupe; Barba, Raquel; Font, Carme; Díaz-Pedroche, María del Carmen; Mazzolai, Lucia; Little, Derek Henry Wallace; Tufano, Antonella; Tafur, Alfonso J.; Siegal, Deborah; Lip, Gregory Y.H.; Monreal, Manuel; for the RIETE Investigators (Seminars in Thrombosis and Hemostasis, 2019)
Patients with cirrhosis are not only at an increased risk of bleeding but also at risk of venous thromboembolism (VTE). We sought to determine the clinical characteristics, management, and outcomes after VTE in patients with cirrhosis. We used the data from RIETE (Registro Informatizado de la Enfermedad TromboEmbolica), an international registry of patients with VTE, to compare the outcomes in patients with and without cirrhosis. Main outcomes included all-cause mortality, pulmonary embolism (PE)-related mortality, recurrent VTE, and bleeding. Among 43,611 patients with acute VTE, 187 (0.4%) had cirrhosis. Of these, 184 (98.4%) received anticoagulation for a median of 109 days (interquartile range [IQR]: 43–201 days), most commonly with enoxaparin (median dose: 1.77 [IQR: 1.38–2.00] mg/kg/day). Compared with patients without cirrhosis, those with cirrhosis had a higher rate of all-cause mortality (10.7 vs. 3.4%; odds ratio [OR]: 3.41; 95% confidence interval [CI]: 2.03–5.46) and fatal bleeding (2.1 vs. 0.2%; OR: 13.94; 95% CI: 3.65–37.90) but similar rates of fatal PE (0.5 vs. 0.5%; OR: 1.17; 95% CI: 0.03–6.70). Patients with cirrhosis had a higher rate of all-cause mortality per 100 patient-years of follow-up (58.9 vs. 16.0; hazard ratio [HR]: 3.70; 95% CI: 2.69–4.91). One-year hazard ratio of clinically relevant bleeding (HR: 2.86; 95% CI: 1.91–4.27), fatal bleeding (HR: 8.51; 95% CI: 3.5–20.7), or recurrent VTE (HR: 2.08; 95% CI: 1.00–4.36) was higher in patients with cirrhosis. Cirrhosis is a challenging comorbidity in patients with VTE. Most patients were treated with anticoagulation and had an elevated risk of recurrence, similar risk of fatal PE, and a very high risk of bleeding including fatal bleeds.
Keywords: venous thromboembolism; cirrhosis; bleeding